High prevalence of trimethoprim-resistance cassettes in class 1 and 2 integrons in Senegalese Shigella spp isolates - Amy Gassama Sow; Awa Aïdara-Kane; Olivier Barraud; Martine Gatet; François Denis; Marie Cécile Ploy (Journal of Infection in Developing Countries)
Background: Integrons have a well-established role in the dissemination of resistance among Gram-negative pathogens and are thus a useful marker of antibiotic resistance. Shigellae are noteworthy for their multiple drug resistance, having gradually acquired resistance to most widely use and inexpensive antimicrobial drugs.